“Antinous the good” in Municipium DD in Moesia superior: Architectural analysis of presumed Antinoeion and cult practice - Gavrilović-Vitas Nadežda; Bjelić Igor (Starinar)
In one of the most important mining centres of the ancient Central Balkans, known as Municipium DD (contemporary small town of Sočanica), the remains of a temple dedicated to Emperor Hadrian’s companion, Antinous were discovered along with different epigraphic monuments and archaeological objects. In this paper, through architectural and archaeological analysis, a proposed interpretation of the temple’s appearance and archaeological objects dated to the same period as the temple and discovered in the sacral place or its vicinity, is presented. The interpretation of all finds shows that the 2nd century temple belonged to the Ionic order of temples, which is a significant fact bearing in mind Emperor Hadrian’s respect and love for the Greek culture and art. The temple of the young Bythynian Antinoeion in Municipium DD lasted only briefly (it was presumably later transformed into Jupiter’s temple or a Capitolium) and the imperial effort of spreading the cult of Antinous from the mentioned mining site was carried on not only by the mining administrators and miners, but also other high officials in the city administration, high officials in the Roman army, etc. The establishment of the Antinous cult far away from its heartlands in Asia Minor, Greece and Rome, attests to Hadrian’s continued wish to spread the cult of his companion in all parts of the Imperium and to offer a hellenophonic vision of a heterogeneous Roman Empire.